The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.2196/18598
|View full text |Cite
|
Sign up to set email alerts
|

Technology-Enabled Self-Management of Chronic Obstructive Pulmonary Disease With or Without Asynchronous Remote Monitoring: Randomized Controlled Trial

Abstract: Background Chronic obstructive pulmonary disease (COPD) is a leading cause of mortality and leads to frequent hospital admissions and emergency department (ED) visits. COPD exacerbations are an important patient outcome, and reducing their frequency would result in significant cost savings. Remote monitoring and self-monitoring could both help patients manage their symptoms and reduce the frequency of exacerbations, but they have different resource implications and have not been directly compared. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 43 publications
0
30
0
2
Order By: Relevance
“…Of these studies, 11 were included in the meta-analysis [ 22 , 24 , 45 , 47 , 48 , 50 , 51 , 54 - 57 ]. The remaining 4 studies [ 46 , 49 , 52 , 53 ] were excluded because no available means and SDs were reported or obtained after contacting the authors. A total of 7 studies focused on patients with asthma [ 23 , 25 , 58 - 62 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of these studies, 11 were included in the meta-analysis [ 22 , 24 , 45 , 47 , 48 , 50 , 51 , 54 - 57 ]. The remaining 4 studies [ 46 , 49 , 52 , 53 ] were excluded because no available means and SDs were reported or obtained after contacting the authors. A total of 7 studies focused on patients with asthma [ 23 , 25 , 58 - 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…A total of 15 COPD studies [ 22 , 24 , 45 - 57 ] were published between 2006 and 2020 and were conducted in China (n=5) [ 48 , 54 - 57 ], United States (n=2) [ 24 , 51 ], Denmark (n=2) [ 49 , 52 ], Canada (n=1) [ 53 ], England (n=1) [ 45 ], Spain (n=1) [ 22 ], Germany (n=1) [ 50 ], Australia (n=1) [ 46 ], and 1 in both Spain and Belgium [ 47 ]. The sample size ranged from 39 to 242 (with a total sample size of 1477).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a qualitative substudy of a randomized controlled trial [ 18 ]; both the randomized controlled trial and this qualitative study were conducted at a community-based hospital in a large city in Ontario, Canada, within a respiratory center that treats patients with COPD. The randomized controlled trial investigated the effectiveness of implementing a technology-enabled self-monitoring program or a technology enabled self- and remote-monitoring program in a COPD patient population compared to standard care.…”
Section: Methodsmentioning
confidence: 99%
“…The intervention included home spirometry, reporting of symptoms and side-effects, patient-reported outcomes, information, a medication coach, and online consultations [ 4 ]. In COPD, a three-arm randomised trial evaluating the effectiveness of a remote monitoring and a self-monitoring programme did not show any significant differences in self-management skills, knowledge, symptoms, or healthcare use compared with each other or with a standard care group [ 5 ].…”
mentioning
confidence: 99%